2021
DOI: 10.1002/jso.26477
|View full text |Cite|
|
Sign up to set email alerts
|

Is osseous reattachment of the greater trochanter necessary compared to soft‐tissue‐only abductor repair in proximal femoral megaprosthesis reconstruction?

Abstract: Background One of the challenges to surgical reconstruction following oncologic proximal femur resection is reliable re‐establishment of the abductor mechanism. Surgical and functional outcomes following re‐approximation of the abductor mechanism to a metallic endoprosthetic after tumor resection of the proximal femur have not been well established in the literature. Methods A retrospective review was performed, inclusive of patients who received a proximal femur replacement with a metallic endoprosthesis foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Christ et al reported on a small series of 12 patients who underwent proximal femoral reconstruction with compliant compression fixation and found that hypertrophic bone at the bone-implant interface was not common, as it is in distal femoral reconstructions 22 . Finally, Groundland et al reported that, in patients who underwent proximal femoral endoprosthetic reconstruction, salvage of the greater trochanter for reattachment to the endoprosthesis did not lead to improved function compared with soft-tissue-only abductor repair 29 .…”
Section: Imaging and Perioperative Managementmentioning
confidence: 99%
“…Christ et al reported on a small series of 12 patients who underwent proximal femoral reconstruction with compliant compression fixation and found that hypertrophic bone at the bone-implant interface was not common, as it is in distal femoral reconstructions 22 . Finally, Groundland et al reported that, in patients who underwent proximal femoral endoprosthetic reconstruction, salvage of the greater trochanter for reattachment to the endoprosthesis did not lead to improved function compared with soft-tissue-only abductor repair 29 .…”
Section: Imaging and Perioperative Managementmentioning
confidence: 99%
“…Groundland et al compared the functional results of a soft tissue repair or reattachment of the bony greater trochanter to a prosthesis. Contrary to expectations, the incidence rate of a Trendelenberg gait was lower with the soft tissue repair than with reattachment of the bony greater trochanter [ 19 ]. Assuming that bone integration to the metal surface is occurring, surface modification of the prosthesis appears to provide a low rate of aseptic loosening of the stem [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In all of these procedures, the gastrocnemius flap technique is considered the “gold standard” of reconstruction methods for knee extension [ 18 ]. Additionally, for functional preservation after megaprosthetic replacement of the proximal femur, reconstruction of the gluteus medius muscle is encourage, given that failure of the hip abduction may lead to a Trendelenberg gait [ 19 ]. Groundland et al compared the functional results of a soft tissue repair or reattachment of the bony greater trochanter to a prosthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article by Groundland J, Brown JM, Jones KB, Randall RL, 1 the author names Jeffrey Brown and Kevin Jones have been corrected to read "Jeffrey M. Brown" and "Kevin B. Jones".…”
mentioning
confidence: 99%